2020
DOI: 10.3389/fphys.2020.00654
|View full text |Cite
|
Sign up to set email alerts
|

Serum Exosomal MicroRNA-21, MicroRNA-126, and PTEN Are Novel Biomarkers for Diagnosis of Acute Coronary Syndrome

Abstract: Acute coronary syndrome (ACS) is a serious threat to public health. Based on clinical manifestations, ACS can be classified into unstable angina (UA) pectoris and acute myocardial infarction (AMI). The purpose of this study was to explore the possibility of using serum exosomal microRNA (miR)-126, miR-21, and phosphatase and tensin homolog (PTEN) expression levels as biomarkers of UA and AMI and to investigate whether these levels were positively correlated with the severity of coronary stenosis based on the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 29 publications
1
51
0
Order By: Relevance
“…Moreover, it was demonstrated that exosomal miR-1915-3p, miR-4507, and miR-3656 were decreased in the serum exosomes of AMI patients and these miRNAs were predictive for AMI [ 19 ]. In addition, a recent study found that serum exosomal miR-126 and miR-21 levels were increased in ACS and AMI patients and exosomal miR-126 had a strong correction with the severity of coronary artery stenosis [ 38 ]. The above studies suggest that the expression of circulating exosomal miRNAs is dysregulated in ACS and AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was demonstrated that exosomal miR-1915-3p, miR-4507, and miR-3656 were decreased in the serum exosomes of AMI patients and these miRNAs were predictive for AMI [ 19 ]. In addition, a recent study found that serum exosomal miR-126 and miR-21 levels were increased in ACS and AMI patients and exosomal miR-126 had a strong correction with the severity of coronary artery stenosis [ 38 ]. The above studies suggest that the expression of circulating exosomal miRNAs is dysregulated in ACS and AMI.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Kaplan–Meier survival analysis, the 1-year survival rate of patients with high miR-208a levels decreased significantly compared with low miR-208a level group. Further, Ling et al (2020b) showed that the levels of miR-126 and miR-21 in UA and acute myocardial infarction (AMI) patients are significantly higher than those in healthy controls. According to the Gensini score, circulating exosomal miR-126 levels are positively correlated with coronary stenosis in patients with UA and AMI.…”
Section: Cardiovascular Diseases and Exosomal Mirnasmentioning
confidence: 99%
“…Zhu et al found that hypoxia-elicited mesenchymal stem cellderived exosomes facilitated cardiac repair through miR-125b-mediated prevention of cell death in myocardial infarction [48]. Recently, it showed that serum exosomal microrna-21, microrna-126, and pten are novel biomarkers for diagnosis of acute coronary syndrome [49]. These results demonstrate that exosomal miRNA plays key roles in MI and might provide a novel therapeutic pathway for relieving MI.…”
Section: Discussionmentioning
confidence: 97%